2005
DOI: 10.1248/bpb.28.865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional Chinese Medicine on Bone Loss in SAMP6: A Murine Model for Senile Osteoporosis

Abstract: In healthy adults, the amount of bone formation approximately balances the amount of bone resorption. In aged individuals, the balance shifts to favor bone resorption, which can result in debilitating diseases such as osteoporosis. Osteoporosis is a skeletal disorder characterized by compromised bone strength, and predisposes a person to an increased risk of fracture. Bone strength primarily reflects the integration of bone density and bone quality. 1)Osteoporosis is regarded as a heterogeneous disorder with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…The serum total cholesterol and triglyceride levels were determined by enzymatic assays (Richmond, 1973; Tamaoku et al, 1982). The serum PTH and estradiol levels were measured using immunoradiometric assay kit as reported before (Chen et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The serum total cholesterol and triglyceride levels were determined by enzymatic assays (Richmond, 1973; Tamaoku et al, 1982). The serum PTH and estradiol levels were measured using immunoradiometric assay kit as reported before (Chen et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…That is, as shown by the MRT ab values of calcium, the rate and is in accordance with previous clinical usage and studies [12][13][14] . For example, Hidaka et al 13) showed that Unkei-to, Hachimi-jiogan, and Juzen-taiho-to are as effective as 17ß-estradiol in preventing the development of bone loss in OVX rats, while Chen et al 15) determined that Hachimi-jio-gan and Juzen-taiho-to are effective in preventing bone loss in SAMP6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were randomly divided into two groups of sham-operated (SHAM) and OVX mice. After the mice were anesthetized by ether, SHAM mice were bilaterally nonovariectomized, but the OVX group was bilaterally ovariectomized as previously described [12][13][14][15][16][17] . The mice had free access to food and water during the conditioning period of 4 weeks.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations